Effect of Design Engine Room Layout on Self-Righting System-Case Study: Fast Boat - Muhammad Badrus Zaman; Achmad Baidowi; Achmad Ishlahul Fanany (Institut Teknologi Sepuluh Nopember, 2019)
The reliable of the engine room design can affect the success of the ship both in terms of the propulsion nor the self-righting. The design of engine room is one aspect of being able to apply self-righting capabilities. There is an innovation for the development of closed fast boats with self-righting capabilities which have not yet been found in Indonesia. Self-righting is the ability of the ship to be able to return to its original position after experiencing a rolling of 180 °. The design of engine room using the inherent self-righting method is one method to be able to apply self-righting capabilities. The focus of this research is to study the effect of the gravity point on the engine room longitudinally, vertically and transverse on the ability of self-righting. In the engine room obtained LCG 4,044 m, TCG 0.006 m and VCG 0.830 m. The self-righting simulation is divided based on 5 load case conditions. The condition of load case 1 the value is max GZ 0.732 at 51.8 °. The condition of load case 2 the value is max GZ 0.672 at 70 °. The condition of load case 3 the value is max GZ 0.577 at 61.8 °. The condition of load case 4 the value is max GZ 0.687 at 69.1 °. The condition of load case 5 the value is max GZ 0.596 at 59.1 °. At the 5 load case conditions has comply the HSC 2000 code stability criteria and can apply self-righting ability because it comply the requirements of having a positive GZ value of 180 °.